Spontaneous bilateral compartment syndrome in a HIV-positive patient. (17th December 2013) - Davidson, Donald James; Shaukat, Yasir Mehmood; Jenabzadeh, Reza; Gupte, Chinmay M
Abstract : Spontaneous bilateral compartment syndrome is a very rare condition but one which requires swift diagnosis and urgent surgical decompression by fasciotomies in order to achieve the best outcome. We present the case of a 31-year-old HIV-positive man. The case highlights the perils of being sidetracked by an atypical clinical history instead of acting on the classical clinical examination findings. We will discuss the presentation and management of this patient, review the literature and highlight the key learning points. The most important learning point being that no matter how atypical the history, if a patient presents with limb pain out of proportion to the injury (with or without pain on passive stretch), sensory changes and a loss of motor power, then a diagnosis of acute compartment syndrome must be considered.